Generic energy production model for smart grid emulation = Ogólny model producenta energii dla emulatora inteligentnych sieci energetycznych - Krysik, Miłosz; Rybski, Ryszard; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This work describes the progress towards creating a model of energy production block to be applied in a smart grid emulator. This block allows reflecting the behavior of many energy production cases and by that enables defining multiple test scenarios for evaluating energy management algorithms. The model is configurable and the behavior is adjustable in run-time.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne